2005
DOI: 10.1002/jclp.20237
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of mindfulness

Abstract: Recently, the psychological construct mindfulness has received a great deal of attention. The majority of research has focused on clinical studies to evaluate the efficacy of mindfulness-based interventions. This line of research has led to promising data suggesting mindfulness-based interventions are effective for treatment of both psychological and physical symptoms. However, an equally important direction for future research is to investigate questions concerning mechanisms of action underlying mindfulness-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

92
2,498
7
125

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 2,856 publications
(2,722 citation statements)
references
References 26 publications
92
2,498
7
125
Order By: Relevance
“…This increased attendance to, and awareness of, thoughts and emotions is purported to enable the individual to observe their thoughts and feelings as they arise in the mind without engaging with them; thereby allowing greater control over thinking (Williams & Penman, 2011). Shapiro et al (2006) suggested that mindfulness results in a shift of perspective -which they labelled 'reperceiving' -which facilitates a capacity for individuals to see situations as they are in the moment, responding accordingly; instead of with reactionary thoughts and emotions triggered by prior habit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This increased attendance to, and awareness of, thoughts and emotions is purported to enable the individual to observe their thoughts and feelings as they arise in the mind without engaging with them; thereby allowing greater control over thinking (Williams & Penman, 2011). Shapiro et al (2006) suggested that mindfulness results in a shift of perspective -which they labelled 'reperceiving' -which facilitates a capacity for individuals to see situations as they are in the moment, responding accordingly; instead of with reactionary thoughts and emotions triggered by prior habit.…”
Section: Discussionmentioning
confidence: 99%
“…Shapiro, Carlson, Astin, & Freedman (2006) suggest two approaches to assessing mechanisms of change in mindfulness-based intervention studies. Firstly, they suggest that dismantle (tease apart) studies are necessary in order to separate and compare various active ingredients in mindfulness-based interventions.…”
Section: Mindfulnessmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was of course not representative for mindfulness in general. Mindfulness was closely associated with well-being (Brown et al, 2007;Kabat-Zinn, 1990;Shapiro et al, 2006;Tang et al, 2007) and represents the basis for psychotherapeutic concepts such as mindfulness based cognitive therapy for depression (MBCT, Teasdale et al, 1999) or mindfulness based stress reduction (Grossman et al, 2004), which are increasingly applied in psychotherapeutic and psychiatric practice (Allen et al, 2006). Mindfulness has been defined as a receptive attention to and awareness of present experience (Brown and Ryan, 2003).…”
Section: Emotion Introspection and Clinical Implicationsmentioning
confidence: 99%
“…Mindfulness has been defined as a receptive attention to and awareness of present experience (Brown and Ryan, 2003). A related description of mindfulness components comprised intention, attention and a non-judgmental attitude with an awareness for the present moment (Kabat-Zinn, 1990;Shapiro et al, 2006). Mindfulness can be directed to external or to interoceptive experiences.…”
Section: Emotion Introspection and Clinical Implicationsmentioning
confidence: 99%